A new method for the rapid analysis of 1H-Pyrrole-2,5-diones (maleimides) in environmental samples by two-dimensional gas chromatography time-of-flight mass spectrometry. - Naeher, Sebastian; Lengger, S.; Grice, Kliti (2016)
Maleimides (1H-Pyrrole-2,5-diones) are monopyrrolic pigment derivatives with specific alkyl side chains that can be directly linked to their tetrapyrrole precursors, most notably chlorophylls and bacteriochlorophylls. These compounds can be used as palaeoenvironmental indicators such as algal productivity and redox conditions in ancient and modern aquatic systems. Here, we present a new method using two-dimensional gas chromatography time-of-flight mass spectrometry (GC×GC-ToF-MS), which enables the rapid analysis of maleimides in complex mixtures and different matrices (e.g. sediments and soils), therefore largely simplifying the previous intricate maleimide purification protocol. This method also reduces the potential for bias associated with partial losses due to low recovery and the high volatility of maleimides. The maleimide distributions and concentrations obtained by GC×GC-ToF-MS were reproducible and in agreement with the previously used purification procedure followed by analysis with traditional gas chromatography-mass spectrometry (GC-MS). The new method also resolved previously unrecognised, partial coelution of some maleimides with unknown compounds by quantification with the m/z 75 fragment ion. Furthermore, the higher sensitivity enabled the detection of previously unrecognised and preliminarily identified maleimides based on their relative retention times. The new, easier, rapid and more sensitive GC×GC-ToF-MS method greatly facilitates the analysis of maleimides in environmental samples to study tetrapyrrole degradation processes and will further the development of maleimides as biomarkers for palaeoenvironmental reconstructions.